REl entrenamiento perceptivo de bloqueadoras juveniles de voleibol - Saez-Gallego, N. M.; Vila-Maldonado, S.; Abellán, J.; Contreras, O. R (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2018)
This study examines the effectiveness of a training program based on perceptual orientation of attention for improving decision-making and performance in the blocking action of volleyball. 16 youth players were divided into three groups: video (n=6), which received eight perceptual training sessions by video; mixed (n=5), which received only half of the sessions by video, combined with practical training in the field; and control (n=5), which just completed pre-test and post-test tests. Results show how orientation of attention to relevant areas of information improved decision-making of the youth volleyball players because they reduced their reaction time (F(1,13)=9,237, p=0,009, ?p2=0,415) maintaining the same percentage of success. However, the practice on the field is necessary to achieve transfer those learning to the real game, because only mixed group improves the percentage of success in the field performance test (F(2,13)=8,608, p=0,004, ?p2=0,570; t(4)=-6,216, p=0,003).